Overview of the nomenclature and network of contributors to the development of bioreactors for human gut simulation using bibliometric tools: a fragmented landscape - Sanabria,J; Egan,S; Masuda,R; Lee,AJ; Gibson,GR; Nicholson,JK; Wist,J; Holmes,E (Journal of Agricultural and Food Chemistry, 2022)
The evolution of complex in vitro models of the human gastrointestinal system to interrogate the biochemical functionality of the gut microbiome has augmented our understanding of its role in human physiology and pathology. With 5718 authors from 52 countries, gut bioreactor research reflects the growing awareness of our need to understand the contribution of the gut microbiome to human health. Although a large body of knowledge has been generated from in vitro models, it is scattered and defined by application-specific terminologies. To better grasp the capacity of bioreactors and further our knowledge of the human gastrointestinal system, we have conducted a cross-field bibliometric search and mapped the evolution of human gastrointestinal in vitro research. We present reference material with the aim of identifying key authors and bioreactor types to enable researchers to make decisions regarding the choice of method for simulating the human gut in the context of microbiome functionality.